PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER PADA MODEL PEMBELAJARAN PENEMUAN TERBIMBING (GUIDED DISCOVERY) POKOK BAHASANTEOREMA PYTHAGORAS UNTUK SMP KELAS VIII - Rohisah, Verial; Sunardi, S; Pambudi, Didik Sugeng (KadikmA, 2014)
Abstract: The research purpose is to know the process and the result ofdevelopment of mathematics learning instruments based on character at guided discovery learning forTheorem of Pythagorastopic at eightgrade of junior high school. Learning instrumentsdevelopment model refers to 4D Thiagarajanmodels which has 4 steps namely define, design, develop, and disseminate.This research has fourproducts namely lesson plan, student book, worksheet, and evaluation test.Based on validation process and tryout,it can be concluded that the learning instruments had fullfiled with validity, practice, and effective criteria. Key words: 4DThiagarajanmodels, guided discovery learning, character, theorem of Pythagoras